The value of beauty for organizations. (10th July 2018) - Ivanaj, Vera; Shrivastava, Paul; Ivanaj, Silvester
Abstract: Despite an increasing body of scientific evidence accumulated over the last 25 years, organizational design thinking has almost c1ompletely ignored the role of beauty on organizational life and performance. Based on a literature review in the fields of organizational aesthetics and management, this article explores ways in which beauty can create value for organizations. It develops an integrative approach, both rational and aesthetic, that helps better understand the contribution of beauty to organizational efficiency and performance. The analysis shows that beauty in organizations can contribute through different organizational elements: resources, outcomes, processes, organization and environment. It also gives some guidelines on how to measure and integrate it into organizations through the concept of ROIB (Return on Investment in Beauty). Finally, the article concludes with some business implications and suggestions for future research. Highlights: Providing a deep literature review on organizational aesthetics. Explaining ways which beauty can create value for organizations. Exploring how the experience of beauty could be transformed into value for organizations. Measuring the direct impact of beauty on the return on investment. Suggesting some specific questions for future research.